D-Dimer and TAT Measurement in Patients with Deep Venous Thrombosis: Utility in Diagnosis and Judgement of Anticoagulant Treatment Effectiveness - Speiser, Wolfgang; Mallek, Reinhold; Koppensteiner, Renate; Andreas, Stümpflen; Kapiotis, Stylianos; Minar, Erich; Ehringer, Herbert; Lechner, Klaus (Thrombosis and Haemostasis, 1990)
The plasma levels of thrombin-antithrombin III-complexes (TAT) and the fibrin split product D-Dimer were measured in 39 patients with phlebographically proven acute DVT: 34 patients had proximal DVT, 5 had calf DVT The sensitivity of D-Dimer and TAT measurements in the diagnosis of proximal DVT was found to be dependent on the duration of symptoms: 0 to 7 days (n = 27): elevated D-Dimer levels (>120 ng/ml) = 1, D-Dimer Latex test positive (>500 ng/ml) = 1, elevated TAT levels (>6 ng/ml) = 0.88. Eight to 14 days (n = 7): elevated D-Dimer levels = 1, D-Dimer Latex test positive = 0.33, elevated TAT levels = 0.66; specificity: elevated D-Dimer: 0.48, D-Dimer Latex test: 1, elevated TAT: 0.76. Calf DVT patients (n = 5) had elevated D-Dimer levels, negative Latex tests and 3 of them had normal TAT values. Hemostatic and fibrinolytic parameters were also determined in 13 patients during heparin treatment of proximal DVT. Elevated D-Dimer and TAT levels rapidly decreased after initiation of anticoagulant therapy. In 2 of 13 patients a marked increase in D-Dimer and TAT levels was observed in periods of ineffective heparinization, documented by normal or only slightly prolonged thrombin clotting times. We conclude from our results that 1) D-Dimer El A measurement, in contrast to TAT measurement, shows a very high sensitivity in the diagnosis of DVT, 2) due to low specificity this test can only be used to exclude thrombosis in patients with suspected DVT, and 3) the determination of the plasma levels of D-Dimer and TAT may be useful for judging the effect of anticoagulant treatment on thrombotic processes.